Synthesis, characterization, and interfacial properties of an oligomeric, cationic fluorooxetane - Rao, Ashwin (Langmuir : the ACS journal of surfaces and colloids, 2006)
The synthesis and characterization of a cationic oligo(fluorooxetane) surfactant with pendant -C4F9 groups are reported. Molecular area demand at saturation was determined to be 55.6 +/- 0.3 angstroms2/molecule and characteristic of an oligomer. The adsorption of the cationic oligo(fluorooxetane) to the air-water interface appears to be diffusion-limited, and dilational rheological properties of the adsorbed molecules are representative of a "soluble" monolayer. Adsorption dynamics have been measured yielding diffusion coefficients that are dependent on concentration and in the 10(-7)-10(-8) cm2/s range. Complex moduli from dilational interfacial rheological measurements as a function of oscillation frequency were well fitted to the Lucassen-van den Tempel equation, providing an estimate of the Gibbs elasticity. The combination of the oligomeric nature of the fluorosurfactant, short perfluoroalkyl chain and its interfacial properties suggests that this synthetic approach is an attractive route to the development of fluorinated surfactants that avoid the environmental concerns of small-molecule, long perfluoroalkyl-chain surfactants